Answers

2016-03-20T19:14:07+05:30
Then,common difference between will be same
p+10-2p=3p+2-(p+10)
10-p=3p+2-p-10
18=3p
6=p
1 5 1
hope it helps...
check ur answer again
answer is 6
i m sorry for wrong answer ....
The Brainliest Answer!
  • Brainly User
2016-03-20T19:18:53+05:30

we know that a2-a1 = a3-a2

so here 3p+2-(p+10) = p+10-2p

3p+2-p-10 = 10-p

2p-8 = 10-p

2p+p = 10+8

3p = 18

therefore, p=6

we can even verify the answer by putting value of p in these terms

Now plz mark it as Brainliest answer plz

1 5 1